2014
DOI: 10.1190/int-2013-0137.1
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution acoustic impedance inversion to characterize turbidites at Marlim Field, Campos Basin, Brazil

Abstract: Seismic inversion is routinely used to determine rock properties, such as acoustic impedance and porosity, from seismic data. Nonuniqueness of the solutions is a major issue. A good strategy to reduce this inherent ambiguity of the inversion procedure is to introduce stratigraphic and structural information a priori to better construct the low-frequency background model. This is particularly relevant when studying heterogeneous deepwater turbidite reservoirs that form prolific, but complex, hydrocarbon plays i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…We have built an integrated database in an open-source seismic platform and loaded the wells' information (stratigraphic markers and well-log curves), the dip-steering (DS) filtered seismic data and the main stratigraphic horizons interpreted by Nascimento et al (2014). Those authors have shown that the DS filtered data, in which random spurious noises were attenuated, highlight the main reflections related to stratigraphy and therefore they would be more amenable to interpretation.…”
Section: 000mentioning
confidence: 99%
See 3 more Smart Citations
“…We have built an integrated database in an open-source seismic platform and loaded the wells' information (stratigraphic markers and well-log curves), the dip-steering (DS) filtered seismic data and the main stratigraphic horizons interpreted by Nascimento et al (2014). Those authors have shown that the DS filtered data, in which random spurious noises were attenuated, highlight the main reflections related to stratigraphy and therefore they would be more amenable to interpretation.…”
Section: 000mentioning
confidence: 99%
“…To that end, we follow the interpretation of Nascimento et al (2014), that described the reservoir facies with the acoustic impedance lower-equal than 5,700 m/s.g/cm 3 and porosity in the 0.26-0.32% range.…”
Section: Anomalous Resistivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Inversion of seismic data is widely used in investigation of hydrocarbons to estimate reservoir geometry and petrophysical feature. High resolution pseudoacoustic impedance sections allow detailed lithology-fluid prediction at various stages of the reservoir life cycle [8]. The benefit of the inversion is that the seismic resolution is increased and pseudoacoustic impedance is closely connected to acoustic impedance of layers, so geological interpretation is more comfortable.…”
Section: Introductionmentioning
confidence: 99%